(untitled) (International Journal of Innovative Technologies in Economy, 2020)
Regional economic integration has become inevitable to promote the further development of regional economy in China and Mongolia. Since China’s reform and opening up and Mongolia’s democratic revolution, China Mongolia regional economic cooperation has been developing continuously. This paper summarizes the trend of economic cooperation between China and Mongolia through the analysis of economic and trade cooperation between China and Mongolia and the influencing factors of regional economy.